Barriers to and opportunities for the uptake of soil carbon management practices in European sustainable agricultural production. Issue 9 (20th October 2020) - Mills, Jane; Ingram, Julie; Dibari, Camilla; Merante, Paolo; Karaczun, Zbigniew; Molnar, Andras; Sánchez, Berta; Iglesias, Ana; Ghaley, Bhim Bahadur
ABSTRACT: Soil carbon management practices are those that add and maintain organic carbon in the soil. These agricultural practices can potentially both contribute to climate change mitigation and increase the soil's resilience to physical and biological stresses. The paper draws on research findings from five regions across Europe to identify regionally-specific barriers to and opportunities for the adoption of soil carbon management practices. Data were derived from 50 interviews with policy-makers and advisers and 5 stakeholder workshops in Denmark, Italy, Hungary, Poland and Spain. Several barriers to the uptake of soil carbon management practices were common across all regions, however, regional variations were also identified highlighting the importance of understanding the context into which these practices are introduced. Key barriers related to existing biophysical conditions, lack of financial support, farmer knowledge and experience, and the quality of the advisory service. Opportunities included providing economic incentives, harmonizing regulation, supporting long term thinking and planning for resilience and providing good quality advice. We conclude that in addition to persuasive mechanisms for encouraging the adoption of these practices, what is required is a more process-oriented approach that focuses on a series of experiential changes and fosters farmer learning through interactive models of communicative intervention.